Annotated translation of al-madkhal fi ‘ilmil-farà'id (a simplined guide to the islamic law of inheritance) (2016)
Annotated Translation of Al-Madkhal fi'Umil-Farà'id (A simplified guide lo the Islamic law of inheritance), a book Written by Al-Sayyid ‘Ali bn Abi Bakr Al-Muthanna bn Alhaj Abdullahi Nyass Al- Kawlakhl Al-Tijani; May Allah be pleased with all of them (Amin). Many nuclear and extended Muslim families are in disarray and live in fracas after the deceased of a member due to the sharing of his or her property meant for the heirs. Therefore, some issues arise from inheritance provoke emotions and escalate irrational behaviour among the heirs. Consequently, many peaceful homes were turned into chaos be it the wife or husband, father or mother, son or daughter. The book simplified the proportion allotted to each of the beneficiaries in the family. It will definitely guide young and old English audience on how the property of a departed soul could be shared in accordance with the sources of Islamic law. Leading questions were supplied at the end of the book which could be regarded as a self assessment for the reader.